音叉を用いた振動覚検査による転倒予測の有用性 - 吉川 義之; 福林 秀幸; 高尾 篤; TAKEUCHI Shin; 松田 一浩; 安川 達哉; 梶田 博之; 杉元 雅晴 (理学療法学, 2010)
Purpose: The purpose of this study was to ascertain whether we could predict falls by the examination of vibration sense using a tuning fork. Subject: The subjects were 62 community-dwelling elderly outpatients and day-care clients who could walk by themselves, and who had no disorders of cognitive function on the central nervous system. Methods: We assessed them with an examination of vibration sense using a tuning fork and three performance tests (Timed “Up & Go” test, Modified functional reach test, Timed 10m walk test). In addition, subjects were monitored for six months after those assessments to learn whether they experienced a fall. They were then divided into a “fallers” group and a “non-fallers” group, and the measured values were compared. We calculated the cutoff value with Receiver Operating Characteristic (ROC) curve analysis on each performance test and vibration sense. Results: There were 22 fallers (35.5%) during the six months, and the results for vibration sense of the non-fallers group were superior to those of the fallers group. The area under the ROC curve of vibration sense was equal to that of performance tests (0.83). The degree of sensitivity of vibration sense to falls was 77% (specificity: 68%, accuracy: 71%) when the cutoff value was estimated as 5.5 seconds. Conclusion: The results suggested that the examination of vibration sense using a tuning fork is useful for fall prediction. 【目的】本研究の目的は，音叉を用いた振動覚検査で転倒予測が可能であるかを検討することである。【対象】認知症および中枢神経疾患を除外した，歩行が可能な当院外来患者，通所リハビリテーション利用者で6ヵ月間追跡調査が可能であった62名である。【方法】音叉を用いた振動覚検査とTimed “Up & Go” Test，10m自由歩行時間，Modified-Functional Reach Testの4項目を実施した。転倒は測定日より6ヵ月間追跡し有無を確認した。統計処理は，転倒の有無により転倒群と非転倒群に分け比較を行った。また，各検査についてはROC曲線からカットオフ値を求め，精度を確認した。【結果】測定後6ヵ月間に転倒した対象者は22名（転倒率：35.5%）であった。転倒群と非転倒群の比較では，すべての検査において非転倒群の成績が有意に優れていた。ROC曲線の曲線下面積では，振動覚検査が0.83で，他の検査と同等であった。振動覚検査のカットオフ値については5.5秒であり，感度は77%，特異度は68%，正答率は71%であった。【結語】音叉を用いた振動覚検査は，転倒予測の検査として有用であった。